Susceptibility of sour cherry cultivars to isolates of Monilia laxa (Ehrenbergh) Saccardo et Voglino - Sződi, Sz.; Rozsnyay, Zs.; Rózsa, E.; Túróczi, Gy. (International Journal of Horticultural Science, 2008)
In this study, the susceptibility of 7 commercially important sour cherry cultivars to Monilinia laxa was studied. Artificial inoculation was made with M. laxa isolates, which were isolated from different woody plants. Artificial inoculation was prepared in the laboratory and in the field. In laboratory, flowers of sour cherries while in the field, the two-year old twigs were inoculated in 2006 and 2007. According to results of stigmata inoculation, there were infection ability differences among the isolates originated from five different stone fruit host. Cultivars could be sorted into two susceptibility groups. In the field, twig inoculation in 2007 was made at blossom period and in 2007 at harvest. Seven sour cherry cultivars were inoculated with 8-day-old mycelial culture of M. laxa originated from sour cherry and almond. The agressivity and pathogenicity of the two isolates were measured by the degree of floem death: Results showed that year and phenological stage considerably influenced the degree of symptoms caused by the fungus. After artificial inoculation, tissue death progression was studied by fluorescent microscope. According to results, sour cherry cultivars were sorted into disease susceptibility groups. Susceptibility orders were identical to results on stigmata inoculation.